(untitled) (Applied Biological Research, 2023)
Artemisinin (quinzhees) and its derivatives is a natural compound isolated from Artemisia annua which draws its interest in the treatment of drug resistant malaria. The current study was aimed to study the sesquiterpene compounds by using GCMS and to determine thecontents of artemisinin derivative compounds. This paper also emphasized on the quantification of artemether by using HPLC method from a few selected Artemisia species (A. annua, A. japonica, A. nilagirica, A. pallens and A. abrotanum) from different localities of Karnataka (India). In GCMS the relative percentage and amount of each component was calculated by comparing its average peak area to the total area. Data handling was done using Xcaliber software. In HPLC technique, the artemether content was established by Waters 510 Isocratic System with C18 column. In total, 23 components were identified in GC-MS with major constituents as arteannuin b (51%), davana ether (8.3%), davanone (5%), β-eudesmol (72%), pallensin (27%) and cis-hydroxy davanone (85%). In HPLC, artemether was found in all plants in the range of 0.6-6.0 mg, except A. jopanica. However, the present study validates the ethno-medicinal use of artemisinin and its derivatives in malaria treatment.